Strategi Marketing Mix untuk Meningkatkan Volume Penjualan di Toko Elektronik di Denpasar - Nyoman Sri Manik Parasari; Charlie Sarchan Indrawan; I Putu Dharmawan Pradhana; A.A. Gede Putra Pemayun (Universitas Pendidikan Indonesia, 2023)
Indrawan Elektronik Denpasar is one of the stores in Denpasar that sells electrical goods. In contrast to stores that offer electronic items in Denpasar, Polytron is the sole brand available there. As a result, Indrawan Elektronik Denpasar needs a strong marketing plan to stand out from the competition. The marketing mix is the approach used to produce a rise in consumer sales volume. This study uses descriptive qualitative methodology for its data. The following data gathering methods were employed in this study: interviews, observation, and documentation. Despite the planning that went into the marketing mix strategy used at the store, promotion was one of the elements that was lacking. The marketing mix strategy used in the store is as follows: despite the lack of promotions, pricing and discounts are applied to improve sales volume, and the company's location is advantageous in supporting sales activities, product demand rises monthly.